Controle, espionagem e expurgo: os diversos espectros repressivos na Universidade Federal do Ceará (1964-1973) - Oliveira, Jônathan Assunção (2021)
The civil-military dictatorship for 21 years carried out cassations, arrests, persecutions, tortures and purges of subversive groups through the National Information System (SISNI), the result of a governmental mindset to control and standardize society through a wide repressive spectrum. Decree-law 8,159, dated Jan.1991, allowed access to public documents, resulting in several researches and fields of study that intended to understand the impacts and the functioning of Organs repressive organs operating in authoritarian Brazil in the 1960s and 1980s. The research sought to understand the performance and impacts caused by the Security and Information Communities, installed secretly in federal universities since 1970. We will use the concepts of revolutionary political police and legal espionage to apprehend the forms of espionage and elimination of opposition groups practiced by the Special Security and Information Advisory Services (AESI), Security and Information Divisions (DSI) and the National Information Service (SNI) infiltrated at the Federal University of Ceará (UFC). The research methodology consisted of analyzing the documentation produced by the organs of the national repressive Security apparatus (DIOPS, DOI-CODI, DOPS) and Information (SNI, DSI, AESI-UFC, CIE, CISA, CENIMAR) belonging to the Archive's collection Nacional (SIAN), in addition to edited military repressive decrees and the Minutes of the UFC University Council (CONSUNIUFC) to understand the functioning of the repressive period of 1964-1977. It also aims to interpret the surveillance mechanisms instituted on supposedly subversive student activities, creating repressive mechanisms that directly affected sectors of the student and faculty bodies at the Federal University of Ceará (UFC). These mechanisms resulted in the interference, control and intervention of academic activities: assemblies, meetings of academic directors, causing the expulsion of students, dismissal of teachers, invasions in suspicious courses and the arrest of subversives in the UFC facilities by the decree of Decree-Law nº 477/69 and 510/69.